Rancang Bangun Purwarupa Monitoring Arus Bocor Pada Kabel Grounding Trafo Incoming 20 KV di Gardu Induk Nusa Dua Berbasis Internet Of Things - Dharma Bagus Saputra; Aditya Pradana; Josua Febrian Togatorop; Lie Jasa; Rukmi Sari Hartati (Jurnal Informatika, 2024)
Failure of the grounding isolation on the 20 kV transformer incoming cable, resulting in leakage current. The leakage current on the grounding cable can change periodically, so an accurate and real-time monitoring system is required to protect the power transformer equipment and facilitate responsive handling. Therefore, an Internet of Things-based monitoring device is needed that can detect the magnitude of the leakage current present on the 20 kV secondary side of the transformer using an ESP8266 microcontroller and Arduino UNO R3 as the brain of the monitoring system, which controls and processes data from the input to output components. The SCT-013 current sensor is used to measure the AC current on the transformer incoming 20 kV grounding cable without requiring cable cutting, and the Arduino IDE is used to configure the program on the ESP8266 microcontroller to work according to the desired configuration. The results of the prototype testing using the ESP826 and Arduino UNO R3 microcontrollers and the SCT-013 current sensor have shown that the system can work well and the monitoring has been successfully implemented with real-time current monitoring using the Thinkspeak and Blynk platforms. The testing also proved that the SCT-013 current monitoring device can provide a comparison of the test results and measurements with a Tang Ampere, and the data obtained shows that the real-time SCT-013 current monitoring device is accurate, with an average reading error of less than 3% from the SCT-013 non-linearity specification, with a total reading error percentage of 2.0%. Additionally, the current monitoring device is precise, with the lowest standard deviation value of 0.046.